The Role of Indigenous Agricultural Systems in Strengthening Ecological and Social Resilience of Local Communities - Yohanes Kamakaula; Fatima Soares (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. Indigenous agricultural systems represent centuries of accumulated ecological knowledge and cultural practice, often sustaining biodiversity, food security, and community cohesion in challenging environments. Despite their recognized value, limited research integrates both ecological and social dimensions to understand their role in resilience. Purpose. This study investigates how indigenous agricultural systems contribute to strengthening ecological and social resilience in local communities, using a holistic socio-ecological framework. Method. A mixed-methods design combined quantitative ecological assessments with qualitative ethnographic research in three communities: Kailapa Valley, Seranguna Highlands, and Tumbira Coastal Plains. Data collection involved household surveys (n=180), key informant interviews (n=36), focus group discussions, and field-based ecological measurements. Results. Findings reveal that high crop diversity, robust soil fertility management, and functional water infrastructure are closely linked with cooperative labor systems, seed exchange networks, and inclusive decision-making processes. Communities exhibiting strong integration of ecological and social practices demonstrated greater adaptive capacity to environmental variability and economic fluctuations. Case study evidence from Kailapa Valley illustrates the synergistic relationship between governance, cultural rituals, and ecological stewardship. Conclusion. Indigenous agricultural systems operate as co-evolved socio-ecological frameworks that enhance resilience through the interdependence of environmental health and social cooperation. Preserving these systems offers a pathway for sustainable development and climate adaptation. The research advances the understanding of resilience by uniting ecological and social dimensions within a single analytical framework, offering methodological guidance for cross-disciplinary studies of traditional agriculture.